L'Isola dei Famosi: Minority politics in Italy via reality television. Issue 1 (1st March 2015) - Cosentino, Gabriele
This article interrogates the potential for reality television shows to serve as outlets for the representation of social and political issues on Italian television. To this end the article offers an in-depth critical analysis of selected episodes of two editions of the popular Italian reality television show L'Isola dei Famosi/Celebrity Island, which aired on public television channel RAI 2 from 2003 to 2012. In particular, the article focuses on the 2008 season, characterized by the victory of Vladimir Luxuria, a transgender entertainer and activist of the Lesbian, Gay, Bisexual, Transexual and Queer (LGBTQ) community in Italy; and on the 2010 season, which featured the participation of homosexual writer Aldo Busi, who was expelled from the show for his remarks against religious and political institutions. A close analysis of these two seasons reveals the ways in which popular prime time entertainment programmes such as a reality television show can generate significant public exposure for marginal identities and controversial political topics.